Friction stir welding with weaving arrangement. (2021) - Balasubramanian, M.; Murali, S.; Jayabalakrishnan, D.
Abstract: Structural materials such as copper and aluminium, with comprehensive properties such as excellent thermal and electrical conductivity, are used in engineering applications. Despite the beneficial actions of aluminium and copper as a composite structure, the development of such dissimilar combinations is more difficult. Some unsolvable problems such as oxidation, tunnels, and fragmentary cracks include the fusion of dissimilar metals or alloys in the joining of Cu and Al alloys using classical methods such as fusion welding and pressure welding. The Friction Stir Welding (FSW) process has been found to be an effective method for joining different metals/alloys in solid-state joining technology to solve these problems. A non-consumable stirring tool is plunged into the base metal joints comprising a profiled pin and shoulder and is made to move in a predefined direction to stir up the bondage between the base metals. A proper stirring of base metals was achieved by tool pin eccentricity in this current investigation.